AHLI WARIS PENGGANTI DALAM KHI DITINJAU DARI PERSPEKTIF GENDER - Deden Hidayat; Siti Masitoh; Deden Inayatullah (LPPM Universitas Bina Bangsa, 2023)
The formulation of the Successor heirs is regulated in article 185 of the Compilation of Islamic Law, this is a legal breakthrough made by the government to uphold the principle of justice in inheritance and a policy of heirs in the division of inheritance for grandchildren who are hindered from obtaining inheritance due to their parents dying first than the heirs or grandparents of both the grandsons of the male transmit and the grandchildren of the female transmitters with a view to the benefit of the life of the brothers. As is the case with the purpose of Islamic law (maqashid al-shari'ah) which is aimed at the benefit of the ummah. One of them is the theory about Al-Maslahah Al-Mursalah which is necessary for the prudence, and benefit of the people